Shariah Based Kindergarten: The Gate of Islamic Virtue - Osman, Adibah Alawiah; Osman, Halimatun Saadiah (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2018)
Abstract - Handling the delivery of kindergarten according to Syariah principle is vital for assessing overall performance. It is important to note that numerous prior researchers have done most of the research which regard towards the Kindergartenâs basic knowledge of Islamic Early Childhood Education (IECE). This journal fits its real purpose by elaborate more into Islamic kindergarten as to enhance in-depth understanding of practical behaviour and syllabusâs approach in order to achieve most accurate delivery of Shariah based kindergarten. This study includes the theory underpinning the practicability of Islamic Kindergarten has on pertaining approach, as they are taking responsibility to promote the learning method beforehand. In particular, the proposed framework of the Shariah Based Kindergarten influences the direction of the religious aims as well as the accurate learning method that is underdeveloped in the religious literature. Such a study should give insights into Shariah Based Kindergarten, an organizational form that acts as the gate of Islamic Virtue.